Organic THz Generators: A Design Strategy for Organic Crystals with Ultralarge Macroscopic Hyperpolarizability - Seok, Jin Hong; Kim, Deokjoong; Kim, Won Tae; Kim, Seung Jun; Yoon, Woojin; Yoon, Ga Eun; Yu, In Cheol; Jazbinsek, Mojca; Kim, Sang Wook; Yun, Hoseop; Kim, Dongwook; Rotermund, Fabian; et al. (Advanced Optical Materials, 2021)
Newly designed halogenated organic quinolinium crystals proposed in this work provide fully optimized molecular ordering for maximizing the optical nonlinearity and high-performance broadband terahertz (THz) wave generation. The ultralarge diagonal optical nonlinearity (almost 300 × 10−30 esu) of the new halogenated crystals is approximately two times larger than that of state-of-the-art pyridinium-based crystals. In contrast, nonhalogenated analogous crystals exhibit very low (or vanishing) diagonal optical nonlinearity. This is attributed to halogen-induced unique interionic interactions and fine-tuning of the space-filling characteristics. In addition, the halogenated crystals show a good ability for bulk crystal growth of few millimeters lateral size with plate-like morphology and high thermal stability that are finally required for real-world applications. The new halogenated quinolinium crystals exhibit excellent THz wave generation characteristics, significantly surpassing the limit of conversion efficiency and spectral bandwidth of inorganic benchmark crystals. A 0.16 mm thick chlorinated crystal generates a 29-times larger THz field than 1.0 mm thick inorganic ZnTe crystals at 1500 nm pump wavelength with a flat and broadband spectrum extending up to ≈8 THz. Therefore, introducing halogen substituents is a potential design strategy for designing new organic crystals showing ultralarge macroscopic hyperpolarizability and high-performance THz wave generation.
Keywords: Broad-band spectrum; Broadband terahertz; Bulk crystal growth; High thermal stability; Hyper-polarizability; Interionic interactions; Optical nonlinearity; Plate-like morphology; electro-optic crystals; halogenated organic crystals; nonlinear optics; THz photonics